Non‐driver gene mutation analysis in a large cohort of polycythemia vera and essential thrombocythemia. (17th October 2022) - Morishita, Soji; Hashimoto, Yoshinori; Furuya, Chiho; Edahiro, Yoko; Ochiai, Tomonori; Shirane, Shuichi; Inano, Tadaaki; Yasuda, Hajime; Ando, Miki; Araki, Marito; Komatsu, Norio
Abstract: Objectives: A proportion of patients with polycythemia vera (PV) and essential thrombocythemia (ET) harbor non‐driver mutations associated with poor prognosis. In this study, we analyzed the frequency of non‐driver mutations in a large Japanese PV and ET cohort. Furthermore, we studied the relationship of these mutations and prognosis in Japanese patients. Methods: We enrolled 843 Japanese patients with PV or ET. Non‐driver mutations were analyzed by target resequencing using next‐generation sequencing. The association of the mutations with the prognosis was estimated using multivariable logistic regression analysis and log‐rank test. Results: Non‐driver mutations were detected in 31.1% and 24.5% patients with PV and ET, respectively. Among them, ASXL1 mutations were identified as a risk factor for leukemic/myelofibrotic transformation in PV and ET patients (hazard ratio: 4.68, p = .006). The higher‐risk groups of the mutation‐enhanced international prognostic system (MIPSS)‐PV and MIPSS‐ET incorporating non‐driver mutations exhibited significantly shorter overall survival compared with the low‐risk group ( p < .001). Conclusions: These results implicate the importance of studying non‐driver mutations for predicting the prognosis and survival of Japanese PV and ET patients.